Factors influencing students ‘achievement: A Structural Equation Modelling Approach - PHATSOMBATH, Sengdao; VANG, Khammee; PHAIYAVONG, Somchay; LAMPHAIPHANH , Ketsalinh; BUOLAKHAM, Sengdala (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research aimed to (1) find out factors that influence the learning of Mathematics (2) examine the relevance of the Structural Equation Model of students ‘achievement developed by researchers and empirical data. A sample was the students in years 5, 6 and 7 at Sobchaek Secondary School, Parkxaeng District, Luangprabang Province, academic year 2018-2019. There were 96 students and 46 of them are females. The independent variables used in this research were 8 variables and 1 dependent variant consisted of Parental promotion, Background Knowledge, Teacher behavior, management behavior, Teacher Student relationship, Motivation of learning out-come, Attitude toward mathematics, reading period and mathematics achievement. SPSS was used in data analysis for basic statistics and AMOS was used for Path analysis in analysis of the causal factor model. The results of analysis were found that: Factors that influenced mathematics achievement of students in years 5 to 7 at Sobchaek Secondary School, Pakxaeng District, Luangprabang Province, academic year 2018-2019 was obvious that students completely achieved and each of the independent variables was in the high level with an ,; compared to the criterion, the level of feedback was very reasonable. The structural equation model of factors influencing students ‘achievement developed by the researchers had goodness-of-fit with the empirical data (Chi-square=4.602, df=9, P-value=0.868, Chi-square/df=0.511, GFI=0.986, RMSEA=0.000). The path of influence between all the variables was related to the statistically significant period 0.05 and learning outcome motivation variables had the greatest indirect effect on students ‘achievement (value 0.243), Students’ basic knowledge variable that had the greatest indirect effect on students ‘achievement (value 0.159) through the motivation variables of learning and time for reading. The motivation variables of learning results had the highest total effect on students ‘achievement (value 0.243). The findings indicate that all factors could predict 10.1% of variance of students ‘achievement.